PENERAPAN TEKNIK HEAD UP 30° TERHADAP PENINGKATAN PERFUSI JARINGAN OTAK PADA PASIEN YANG MENGALAMI CEDERA KEPALA SEDANG - Wahidin, Ngabdi Supraptini (AKPER Pemkab Purworejo, 2020)
Congestive Heart Failure is the inability of the heart to pump enough blood to carry out metabolism to meet the requirements for oxygen and nutrients in other words, it requires an abnormal increase in pressure on the heart to meet the needs of metabolism. The main problem with clients with congestive heart failure is ineffective breathing patterns. To overcome the breathing pattern is giving oxygen therapy. Objective : to determine the description of the management of nursing care to clients with comprehensive congestive heart failure through the nursing process. Method : This type of research is descriptive using a case study approach. The subjects in this study were two clients who experienced congestive heart failure with criteria experiencing shortness of breath and compositional awareness. Results : showed that there were changes in breathing patterns for the better, not experiencing shortness and normal breathing frequency. Conclusion : Nursing problems with ineffective breathing patterns associated with hyperventilation can be overcome with giving oxygen therapy, increased oxygen, to obtain criteria for the results to be achieved.